2021
DOI: 10.1017/s0033291721002063
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable risk factors for inpatient violence in psychiatric hospital: prospective study and prediction model

Abstract: Background Violence perpetrated by psychiatric inpatients is associated with modifiable factors. Current structured approaches to assess inpatient violence risk lack predictive validity and linkage to interventions. Methods Adult psychiatric inpatients on forensic and general wards in three psychiatric hospitals were recruited and followed up prospectively for 6 months. Information on modifiable (dynamic) risk factors were collected every 1–4 weeks, and baseline background factors. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…In this sample, violence was more common among women. Many studies have shown that male sex is a risk factor for violence in the general population, but often not among people with serious mental illnesses (Brucato et al, 2019 ; Rolin et al, 2018 , 2021 ; Steadman et al, 1998 ) and some studies have shown higher rates of violence among women with mental illnesses (Fazel et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this sample, violence was more common among women. Many studies have shown that male sex is a risk factor for violence in the general population, but often not among people with serious mental illnesses (Brucato et al, 2019 ; Rolin et al, 2018 , 2021 ; Steadman et al, 1998 ) and some studies have shown higher rates of violence among women with mental illnesses (Fazel et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, one risk factor that has not been identified in qualitative work but reported in the current study is ‘recency of violence post-sentence’. Some of these clinical factors are contained in other risk assessment tools, such as FoxWeb [ 26 ] which is based around 10 modifiable factors, and has been recently validated [ 27 ]. As with FoVOx, FoxWeb is quick to complete, includes predictors that are reliably coded, and requires little training.…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors can be justified as they provide key targets for clinical intervention, from which people at increased risk could benefit ( 46 ). Additional research on novel approaches to risk assessment is required to incorporate more detailed monitoring of fluctuations in symptoms and dynamic risk factors, although this will likely improve needs management rather than risk prediction ( 59 ).…”
Section: Discussionmentioning
confidence: 99%